2004
DOI: 10.1192/bjp.185.4.298
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of self-reported psychotic symptoms in the British population

Abstract: Self-reported psychotic symptoms are less common in this study than reported elsewhere, because of the measure used. These symptoms have demographic and clinical correlates similar to clinical psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
364
4
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 495 publications
(409 citation statements)
references
References 31 publications
31
364
4
10
Order By: Relevance
“…It was found that certain groups of non-clinical individuals, such as members of new religious movements, reported very similar patterns of unusual experiences and delusional ideation observed in people with psychosis; the important difference was that they experienced significantly less distress and preoccupation with their beliefs (Smith, Riley, & Peters, 2009;Peters, Day, McKenna, & Orbach, 1999). Population surveys confirmed the prevalence rates of self-reported psychotic experiences as being significantly higher than those of clinical psychotic disorders (Johns et al, 2004;Freeman, 2006), showing that psychotic symptoms are not exclusive to people with diagnosable mental health problems.…”
Section: A Dimensional View: the Psychosis Continuummentioning
confidence: 89%
“…It was found that certain groups of non-clinical individuals, such as members of new religious movements, reported very similar patterns of unusual experiences and delusional ideation observed in people with psychosis; the important difference was that they experienced significantly less distress and preoccupation with their beliefs (Smith, Riley, & Peters, 2009;Peters, Day, McKenna, & Orbach, 1999). Population surveys confirmed the prevalence rates of self-reported psychotic experiences as being significantly higher than those of clinical psychotic disorders (Johns et al, 2004;Freeman, 2006), showing that psychotic symptoms are not exclusive to people with diagnosable mental health problems.…”
Section: A Dimensional View: the Psychosis Continuummentioning
confidence: 89%
“…However, it is now widely accepted that psychotic symptoms lie on a continuum with normal experience, that non-clinical and clinical symptoms share the same risk factors and the presence of non-clinical experiences increase the risk of clinical disorder Johns et al, 2004).…”
Section: Limitationsmentioning
confidence: 99%
“…This finding is consistent with cognitive psychological theories about the development of psychotic experiences. Childhood emotional abuse has been found to damage self-representation (Finzi-Dottan and Karu, 2006), causing individuals to believe that other people are hostile and threatening, which may then trigger the onset and maintenance of psychotic experiences (Johns et al, 2004). Support for this theory stems from a recent study that found that negative schematic beliefs about others are particularly associated with paranoia-related symptoms (Gracie et al, 2007).…”
Section: Trauma-related Variables and Psychotic Experiencesmentioning
confidence: 99%